Not lost in host translation: The new roles of long noncoding RNAs in infectious diseases. (28th October 2019) - Reisacher, Caroline; Arbibe, Laurence
Abstract: Long non‐coding RNAs (lncRNAs) play a central role in the regulation of gene expression. Although they were initially described as mRNA‐like transcripts not encoding proteins, global approaches such as ribosome profiling have shown that they frequently associate with ribosomes, opening the possibility that lncRNAs are a source of cryptic translation events with functional roles. Recent studies have shed more light on small ORFs borne by lncRNAs and encoding short peptides potentially involved in infectious immunity. This review outlines the main strategies used to determine the coding potential of lncRNAs and discusses our emerging understanding of the implication of the encoded peptides in infectious diseases.